2015
DOI: 10.1586/14737175.2015.1071191
|View full text |Cite
|
Sign up to set email alerts
|

Music therapy as a non-pharmacological treatment for epilepsy

Abstract: Epilepsy is one of the most common neurological diseases. Currently, the primary methods of treatment include pharmacological and surgical treatment. However, approximately one-third of patients exhibit refractory epilepsy. Therefore, a novel approach to epilepsy treatment is necessary. Several studies have confirmed that music therapy can be effective at reducing seizures and epileptiform discharges, thus providing a new option for clinicians in the treatment of epilepsy. Although the underlying mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 89 publications
(102 reference statements)
0
11
0
1
Order By: Relevance
“…The exact neural mechanisms underlying reducing seizures by listening to music have not been determined yet. The potential theories on the effect of listening to music on central nervous system have been discussed in detail in a number of the previous review work 6,20,36 . A number of studies additionally have suggested a potential mechanism involving activation of different cortical areas while listening to music 4,14,27,37 .…”
Section: Discussionmentioning
confidence: 99%
“…The exact neural mechanisms underlying reducing seizures by listening to music have not been determined yet. The potential theories on the effect of listening to music on central nervous system have been discussed in detail in a number of the previous review work 6,20,36 . A number of studies additionally have suggested a potential mechanism involving activation of different cortical areas while listening to music 4,14,27,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Music therapy recognized as an alternative non-invasive and non-pharmacological therapy for treating epilepsy. The efficacy of music in controlling seizures was first reported by Fernandez et al, by observing in an experiment that a frequency of 1000 Hz is effective in reducing the seizures interval by using the EEG recordings ( Liao et al, 2015 ). Besides that, different studies have reported that listening to Mozart music can affect individual intellectual abilities, which is well-known as the “Mozart effect”.…”
Section: Complementary Therapiesmentioning
confidence: 99%
“…in juvenile and frontal lobe epilepsy. It had been studied that listening to music enhances the dopaminergic activity in basal ganglia i.e., upregulation of its D2 receptors and also stimulation of the release of dopamine ( Liao et al, 2015 , Maguire, 2012 ) Mirror neurons: Different authors have suggested the involvement of mirror neurons in the antiepileptic effect of music. Mirror neurons are discharged when a person performs any motor action like dancing etc.…”
Section: Complementary Therapiesmentioning
confidence: 99%
“…Music showed clinical benefits of reducing acute and chronic pain (25)(26)(27). For epilepsy, there is clinical and preclinical evidence that specific musical compositions exert anticonvulsant effects (4,(28)(29)(30)(31)(32). Clinical studies showed that exposure to Mozart's K.448 sonata in pediatric epilepsy patients, even those with refractory seizures, caused a significant reduction of seizure frequency and epileptiform discharges (33)(34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%